Application of the On Demand system for vehicular decongestion of an avenue in an urban area with high trafficability - Cabrera Duran, Vladimir Eduardo (2024)
It is known that traffic congestion is a major problem that affects various countries. In this way, multiple solutions have been proposed with the aim of reducing this problem. However, they have not been able to mitigate this phenomenon. Due to this, this article presents a proposed solution to the aforementioned problem in order to reduce traffic congestion and improve the passability of an avenue in an urban area without the need to invest large amounts of money as is the case of the construction of road infrastructure. The proposal is based on implementing the On Demand transportation system, which consists of shared taxis that circulate through alternative routes that have been analyzed considering the existing vehicle congestion on the road to be implemented. Likewise, a van-type vehicle fleet was considered with the objective of using the maximum capacity of the vehicles and satisfying the users who travel through the area. In fact, this proposal was simulated using the Synchro 8 software in one of the most congested avenues in the city of Lima, Peru and good results were obtained, with respect to the indicators that were evaluated according to the HCM 2010, which are the following: Delays, level of service and intersection capacity utilization (ICU). The evaluation of the proposal indicates a reduction of more than 50% in vehicle delays, improvements in service levels, of which the most notable was moving from level F to C, and with respect to the ICU level, a 15% decrease. In this way, it is verified that the application of the On Demand transportation system reduces vehicle congestion on the analyzed road, this is evident when comparing the results obtained with those of the current situation.